"Surplus in Man" and the capability-based sustained/total human development. Issue 3 (26th August 2014) - Dilip Dutta, Mr; Dutta, Dilip
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – This paper aims to define a capability-based sustained/total human development, after reviewing both the concept of "Surplus in Man" as the source for achieving the Vedântic ideal of transcendence, and the capability approach to human development. Design/methodology/approach – The capability-based sustained/total human development has been defined by integrating the Vedântic concept of "Surplus in Man" and the deontological theories of morality into the basic approach to capability-based human development. Findings – An answer to the question: "How to apply a holistic approach to our daily life?" is outlined. Practical implications – An example is provided on the role of yoga and meditation as the key initial bridging forces between the Western and Eastern concept of mental health. Also, the recent trend in a morally demanding lifestyle of a section of people in the Western societies for moving towards a galloping spiritual pluralism has been exemplified. Originality/value – Role of responsibility of an individual human being along with his or her right has explicitly been emphasized in the approach to capability-based sustained/total human development.